Pengaruh Pemberian Modal Usaha dan Penjualan Terhadap Profitabilitas Usaha Debitur Bank BRI Raden Intan Bandar Lampung - Ara, Igga Yolanda; Nilwan, Afrizal (Jurnal EMT KITA, 2023)
A company's commercial activities are primarily aimed at achieving optimal profits and maintaining its position against industrial competition. An important parameter to evaluate the situation of a company is its level of profitability. The business capital invested, and the level of revenue generated by the business will contribute significantly to achieving maximum profits. This study aims to study the impact of corporate capital and revenue on the business profits of debtors of BRI Raden Intan Bandar Lampung Bank. This study uses a quantitative research method, with a sample of 10 companies that are macro debtors of PT Bank BRI Raden Intan. Financial report data for the period 2017-2021 is used to analyze the sample 50 times. Data analysis was performed using conventional hypothesis testing and hypothesis testing. The results of the study show that company capital has no significant influence on profitability, while sales have a positive and significant impact on profitability. Overall, the variables of business capital and revenue together influence profitability by 42.1% for PT Bank BRI Raden Intan Bandar Lampung's corporate customers in the period 2017-2021.